2013
DOI: 10.1186/1471-2369-14-259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a six-month intradialytic physical ACTIvity program and adequate NUTritional support on protein-energy wasting, physical functioning and quality of life in chronic hemodialysis patients: ACTINUT study protocol for a randomised controlled trial

Abstract: BackgroundProtein-energy wasting (PEW) is common in hemodialysis patients and is a powerful predictor of morbidity and mortality. Although much progress has been made in recent years in identifying the causes and pathogenesis of PEW in hemodialysis patients, actual management by nutritional interventions is not always able to correct PEW. Some investigators suggest that physical exercise may increase the anabolic effects of nutritional interventions, and therefore may have a potential to reverse PEW. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 49 publications
(47 reference statements)
0
20
1
8
Order By: Relevance
“…Thus, aerobic exercise may be a promising strategy to decrease visceral fat as well as to build muscle and improve physical functioning. In addition, an RCT of intradialytic cycling is currently underway to evaluate its effects on PEW [55]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, aerobic exercise may be a promising strategy to decrease visceral fat as well as to build muscle and improve physical functioning. In addition, an RCT of intradialytic cycling is currently underway to evaluate its effects on PEW [55]. …”
Section: Introductionmentioning
confidence: 99%
“…The time was steadily increased while maintaining a moderate level of intensity for a minimum of 2 to 3 weeks. The final stage of rehabilitation was the accomplishment of a 35-50-minute ride on the cycle ergometer at a moderate level of intensity [30]. The exercise was carried out until reaching subjective feeling of fatigue (5-6 on the 10 -point Borg scale)…”
Section: Physical Exercise Trainingmentioning
confidence: 99%
“…Nutritional therapies such as enteral nutrition, parenteral nutrition, and oral nutritional supplementation can be used to treat PEW [1]. A list of these studies, along with their reported nutritional outcomes, is provided in Table 1 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The studies designed to establish the benefits of nutritional supplementation on the long-term improvements in overall nutritional status in hemodialysis patients with PEW have yielded encouraging results.…”
Section: Introductionmentioning
confidence: 99%